Seminario Internacional “resistencia a antibióticos”: Amenaza global a la salud pública (Universidad Nacional del Altiplano de Puno, Peru) - Escobar-Mamani, Fortunato (2020)
In the facilities of the National University of the Altiplano of Puno, Peru (University City), from 05 to 07 November 2019, the “International Seminar on Antibiotic Resistance: Global threat to public health 2019” was held. Event financed by the National Council of Science and Technology—CONCYTEC—in order to "spread the problem of antibiotic resistance as a global threat to public health", both on the local and international stage; Regarding the way in which bacteria present in a natural or artificial environment can be transmitted to humans. In them, the viruses that induce infections are not adequately combated, since antibiotics only work against bacteria and not against viruses, a process approached from different positions of the exhibitors that not all causes of infections (colds, flu, cough and bronchitis) are properly treated, which are generally known as antibiotic resistance. Of these, the topics addressed in the event have mostly recommended the need to adopt urgent public policy measures, for common or complex antibiotic-resistant infections do not become fatal. The special edition dedicated to the aforementioned event, in the first part is a description of the problems of antibiotic resistance and its implications; and in the second part, the summary of the main presentations presented at the seminar is transcribed.